Study-related determinants of university graduates’ entrepreneurship - Mariusz Trojak; Paulina Hojda; Sylwia Roszkowska (International Entrepreneurship Review, 2023)
Objective: The study undertook an assessment – unique in Polish conditions – of the factors related to higher education differentiating the group of graduates of the Jagiellonian University (JU) in terms of their professional activity in the context of taking up employment or starting self-employment.